(untitled) (American Journal of Economics and Business Innovation, 2023)
Businesses in the livestock sector which are part of the agricultural business sector are very vulnerable to economic and social impacts. Price fluctuations and currency exchange rates will be felt by breeders, as well as people’s purchasing power which will greatly affect the livestock business sector. Population growth causes a region’s Gross Regional Domestic Product (GRDP) to change. The purpose of this study was to analyze the effect of economic growth and population on the welfare of breeders. This research method uses a quantitative approach that emphasizes the analysis of numerical data processed by statistical methods and literature study. The literature study is related to macroeconomic indicators, namely the population and welfare of breeders. Secondary data uses data from the Subang Regency Livestock and Animal Health Service, the West Java Province Food Security and Livestock Service Office, the Central Bureau of Statistics (BPS) Subang Regency, and West Java BPS as well as data from related journals and articles. Data analysis using multiple regression analysis techniques. The results showed that there was a significant influence between economic growth and population on the welfare of breeders in Subang Regency. This research shows that the welfare of smallholder breeders is influenced by economic growth and population. The higher the economic growth and population of an area, the higher the level of welfare of breeders in that area.